Hubungan Penggunaan Alat Kontrasepsi dalam Rahim (AKDR) dengan Gangguan Menstruasi di RS PKU Aisyiyah Boyolali - Wintartik Wintartik; Heni Purwaningsih; Munaaya Fitriyya (Transformasi: Journal of Economics and Business Management, 2024)
Intrauterine device is one of the long-acting contraceptives made of plastic wrapped in copper that is inserted into the uterus through the vagina to prevent pregnancy. IUD is one of the contraceptives that has high effectiveness. IUD has side effects, namely menstrual disorders, spotting, spulsion, vaginal discharge. to determine the relationship between the use of IUD contraceptives with menstrual disorders. type of research correlative with cross sectional design. This research was conducted at PKU 'Aisyiyah Boyolali Hospital in December 2023. The subjects of this study were 58 IUD birth control acceptors at PKU 'Aisyiyah Boyolali Hospital during April – November. The sampling technique uses purposive sampling. The measuring instrument uses medical records and questionnaires. The data analysis method uses the chi-square test. the majority aged 31-40 years are 73.1%, have a high school education of 43.6%, the majority use a Nova-T IUD of 58.9% and have menstrual disorders as much as 57.1%. The results of the chi-suare test obtained results of nilia p-value 0.000 <0.05, then Ha is accepted so that there is a relationship between the use of contraceptives and menstrual disorders. There is a relationship between the use of intrauterine devices and menstrual disorders at PKU 'Aisyiyah Boyolali Hospital